Multifunctional conductive injection hydrogel OQG and preparation method thereof

By developing a multifunctional conductive injection hydrogel OQG, the combination of quaternary ammonium chitosan, aldehyde-glucan and conductive reducing graphene oxide nanoparticles was solved, and the problem of scar formation during wound healing was achieved quickly. The effects of repairing and reducing scars demonstrate significant antibacterial and antioxidant abilities.

CN119139536APending Publication Date: 2024-12-17THE THIRD PEOPLES HOSPITAL OF HUBEI PROVINCE (ZHONGSHAN HOSPITAL OF HUBEI PROVINCE) +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411015386.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-26
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The wound healing process is complex and often leads to scar formation. The prior art is difficult to effectively accelerate healing and reduce scar formation, especially in the face of wound infections and systemic diseases.

Method used

Develop a multifunctional conductive injection hydrogel OQG to form self-healing, antibacterial, antioxidant and conductive nanoparticles through the combination of quaternary ammonium chitosan, aldehyde-glucan, dopamine and conductive reducing graphene oxide nanoparticles. Characteristic hydrogels used to promote wound healing.

Benefits of technology

The hydrogel demonstrates significant injectability and self-healing, which can quickly repair irregular wounds, reduce infection risk, regulate inflammatory responses, and stimulate tissue regeneration through conductive properties, significantly accelerate wound healing and reduce scar formation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119139536A_ABST
    Figure CN119139536A_ABST
Patent Text Reader

Abstract

According to the multifunctional conductive injection hydrogel OQG provided by the invention, through dynamic Schiff base crosslinking between oxidized dextran (Dextran) and quaternary ammonium salt chitosan (QCS), enhancement by using polydopamine modified reduced graphene oxide (rGO (at) PDA) and loading of polydopamine encapsulated asiaticoside (AC (at) PDA), the obtained hydrogel has injectability, is suitable for irregular wounds, can be quickly self-healed, and has the advantages of good biocompatibility and good biocompatibility. And the wound adhesive force is relatively good. In addition, the composite hydrogel also has antioxidant and antibacterial activity, and can relieve inflammation and prevent infection. The incorporation of conductive reduced graphene oxide further promotes the delivery of endogenous electrical signals, stimulates cell migration and tissue regeneration, while also maintaining the release of AC to modulate collagen deposition and angiogenesis. In-vitro evaluation proves that the hydrogel disclosed by the invention has cell compatibility for promoting cell migration. Rat wound assessment results show that the multifunctional hydrogel can accelerate wound healing, reduce inflammation and reduce scars.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biomedical materials, and in particular relates to a multifunctional conductive injectable hydrogel OQG and a preparation method thereof. Background Art

[0002] Wound healing is a complex and dynamic process that includes four stages: hemostasis, inflammatory response, proliferation, and remodeling. This process requires complex coordination between different cells and bioactive molecules. The healing process usually leads to scar formation. The degree of scarring in adult wounds is more obvious than that in fetuses. This is attributed to the significant differences in fibroblast activity, extracellular matrix composition, and cytokine environment between adult and fetal wounds. In addition, clinical complications such as wound infection and systemic diseases such as diabetes may cause delayed or non-healing of wounds, leading to excessive scar formation. For this reason, people are paying more and more attention to exploring new biomaterials that can achieve targeted healing to promote wound healing and reduce scarring. At present, there are still deficiencies in achieving accelerated healing and minimizing scar formation.

[0003] Therefore, considering the complexity of the wound healing process, it is necessary to develop a multifunctional hydrogel to accelerate wound healing and reduce scar formation. Summary of the invention

[0004] The purpose of the present invention is to provide a multifunctional conductive injectable hydrogel OQG, and providing a preparation method thereof is the second invention purpose of the present invention. The multifunctional conductive injectable hydrogel OQG prepared by the present invention has the characteristics of injectability, self-healing, conductivity, antibacterial activity, antioxidant capacity, etc., and can accelerate wound healing, reduce inflammation, and reduce scarring.

[0005] In order to achieve the above-mentioned invention object, the present invention adopts the following technical solutions:

[0006] A method for preparing a multifunctional conductive injectable hydrogel OQG comprises the following steps:

[0007] 1) adding water to quaternary ammonium salt chitosan QCS, aldehyde-dextran ODex and dopamine DA to obtain QCS solution, ODex solution and DA solution respectively;

[0008] 2) Add rGO@PDA nanoparticles to the QCS solution, mix the DA solution and the ODex solution, and stir at 35-40°C and 500-1000 r / min for 15-20 min to obtain a mixed solution A and a mixed solution B; then mix the two mixed solutions A and B evenly and let stand for 1-3 min.

[0009] Preferably, AC@PDA is also added to the hydrogel.

[0010] Preferably, the mass ratio of AC@PDA to rGO@PDA is 1:(1-10).

[0011] Preferably, the AC@PDA is added directly into the quaternary ammonium salt chitosan QCS solution or the ODex solution.

[0012] Preferably, the AC@PDA nanoparticles are synthesized in two steps; in the first step, dopamine DA is polymerized under alkaline conditions to generate PDA nanoparticles, and the specific steps are: dissolving 180 mg of DA powder in 90 mL of ultrapure water, and adjusting the pH to 8.5 with 1 M sodium hydroxide solution; stirring the obtained mixture at 25°C for 24 hours to form a black precipitate; then centrifuging at 4000 rpm for 15 minutes, collecting the PDA nanoparticles, washing with ultrapure water to remove residual sodium hydroxide, and freeze-drying to obtain a black powder; in the second step, loading the PDA nanoparticles with AC: dispersing 0.2 mg of freeze-dried PDA nanoparticle powder in 10 mL of AC solution to obtain a dispersion suspension, and stirring at 4°C for 2 hours, centrifugally filtering and freeze-drying to obtain AC@PDA nanoparticles, which are stored at 4°C for later use.

[0013] Preferably, in step 1), the preparation step of the quaternary ammonium salt chitosan QCS is: 16g chitosan and 7.2g glycidyl trimethylammonium chloride GTMAC are dispersed in 240mL ultrapure water, stirred and refluxed at 80°C for 36h to obtain a yellow reaction product, dialyzed in ultrapure water for 72h using a 1.4KDa dialysis membrane, and concentrated and freeze-dried to obtain QCS.

[0014] Preferably, in step 1), the aldehyde-glucan ODex is prepared by the following steps: 3.28 g NaIO 4 Add water to get 0.0154M NaIO 4 The solution was gradually added with 400 mL of 1.25 wt / v% dextran aqueous solution Dex. After stirring at room temperature and in the dark for 24 h, an equal amount of ethylene glycol was added to the system to neutralize the remaining NaIO 4 The obtained solution was dialyzed for 3 days and then freeze-dried to obtain ODex; the dialysis was performed using a dialysis membrane with a pore size of 3500Da.

[0015] Preferably, in step 1), the rGO@PDA nanoparticles are prepared by the following steps: 20 mg of reduced graphene oxide (rGO) and 20 mg of dopamine (DA) are dissolved in 40 ml of Tris·HCl buffer (pH=8.5), ultrasonicated for 30-60 min, and vigorously stirred at room temperature for 24 h, the reaction solution is separated, extracted, filtered, and the rGO@PDA complex is collected, and vacuum dried at 60°C for 48 h.

[0016] Preferably, in step 1), the temperature during mixing of quaternary ammonium chitosan QCS is 35-40°C, the stirring speed is 400-600r / min, the mixing time is 6-9h, and aldehyde-glucan ODex and dopamine DA are added with water and shaken at room temperature and protected from light to mix; in step 1), the concentration of the QCS solution is 3wt%, the concentration of the ODex solution is 12.5wt%, and the concentration of the DA solution is 20wt%; and in step 2), the mass ratio of ODex:DA is 6:1, the mass ratio of rGO@PDA nanoparticles to QCS is 1:3, and the mass ratio of ODex of mixed solution B to QCS in mixed solution A is (0.5-1.5):1.

[0017] The present invention further discloses the multifunctional conductive injectable hydrogel OQG prepared by the above preparation method.

[0018] In step 1) of the present invention, quaternary ammonium salt chitosan QCS, aldehyde-glucan ODex and dopamine DA are mixed with water to obtain QCS solution, ODex solution and DA solution. The reason is that the Schiff base reaction (ODex and QCS, ODex and DA) is very fast and reacts to form gel within 1-3 minutes. The solutions are prepared separately so that the sample can be completely dissolved in the solution before the reaction, and the reaction is more uniform when the reaction forms gel.

[0019] Compared with the prior art, the technical effects of the present invention are:

[0020] The present invention develops a novel multifunctional hydrogel, which has injectability, self-healing, conductivity, antibacterial activity, antioxidant capacity and therapeutic effect. The multifunctional conductive injectable hydrogel OQG is prepared by a dynamic Schiff base bond between oxidized dextran and quaternary ammonium salt chitosan, combined with conductive reduced graphene oxide and dopamine nanoparticles. The obtained hydrogel has outstanding injectability and self-healing properties, is convenient for application to irregular wound sites, achieves rapid self-repair, and maintains the integrity of the gel, as well as strong tissue adhesion, which can ensure close contact with the wound. In addition, the hydrogel has intrinsic antibacterial and antioxidant activity, can reduce the risk of infection, regulate inflammatory response, and its conductivity can stimulate tissue regeneration. In vitro experiments show that the cell compatibility of the hydrogel and its ability to accelerate cell migration are more conducive to wound healing. When applied to full-thickness wounds of rats, the multifunctional hydrogel of the present invention can promote accelerated wound healing and minimize scar formation compared with untreated wounds. The multifunctional hydrogel with AC@PDA added in the present invention also shows the potential in enhancing wound healing and achieving scar-free skin regeneration, thus providing a possibility for solving the complexity of the wound healing process. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:

[0022] Figure 1 Schematic diagram of the synthesis of (a) ODex and ODex-DA, (b) QCS, (c) rGO@PDA, and (d) AC@PDA.

[0023] Figure 2 FT-IR of (a) Dex and ODex, (b) CS and QCS, (c) rGO, DA and rGO@PDA nanoparticles, (d) OQG hydrogel; (e) Dex and ODex (D 2 O), (f) DA, ODex and ODEx-DA (D 2 O), and (g) CS, QCS (D 2 O) 1 H NMR; (h) TEM of GO (i), PDA (ii) and rGO@PDA (iii) nanoparticles; (i) SEM of OQG hydrogel, and (j) statistical pore size distribution analysis. (k) XPS spectrum of rGO@PDA nanoparticles, and for O1s scan (ii), C1s scan (iii) and N1s scan (iv);

[0024] Figure 3 (a) Swelling properties of OQG hydrogel in purified water (***p<0.001). (b) Photographs of the adhesion of OQG hydrogel on plastic, glass, rubber, human skin and finger joints; The rheological properties of OQG hydrogel were studied using a rheometer, and the G' and G" of OQG hydrogel were recorded under (c) frequency, (d) time and strain. The photo inserted in (c) shows the prepared OQG hydrogel; The self-healing properties of the hydrogel were tested using (h) a rheometer (OQG hydrogel alternating strain between 1% and 100%) and (i) a photo showing the self-healing properties of the hydrogel; (j) OQG hydrogel The relationship between the viscosity of the gel and the shear rate, and the inset is an illustration of the injection of the hydrogel by a syringe; Since all OQG hydrogels have very similar rheological self-healing and viscosity behaviors, only the data of sample OQG3 hydrogel in (h) and (j) are shown; (k) The effect of OQG hydrogel in scavenging DPPH (0.5h), (***p<0.001); (l) The conductivity of OQG hydrogel in the circuit; (m) The conductivity of OQG hydrogel, (***p<0.001);

[0025] Figure 4 The antibacterial properties of OQG hydrogel against Escherichia coli and Staphylococcus aureus were evaluated; Figure 4(a) Photographs of OQG hydrogels incubated with E. coli and S. aureus for 24 h. (b) Radius of inhibition zone of OQG hydrogels against E. coli and S. aureus. (c) Inhibition rate of hydrogels against E. coli and S. aureus in LB agar liquid medium for 12 h, and the inset is a photograph of sample OQG1 in LB agar liquid medium. The biocompatibility of OQG hydrogels was determined by CCK-8 method, fluorescence microscopy method and cell scratch method. (d) Fluorescence microscopy images of OQG1, OQG2 and OQG3 hydrogels cultured with NIH-3T3 cells after 1 day and (e) samples stained with Calcein-AM / PI after 3 days, 200 μm. (f) CCK-8 test results of OQG3 hydrogel co-cultured with NIH-3T3 cells for 1, 3 and 5 days. (c) Scratch test results of NIH-3T3 cells scratched for 12 h. The black line indicates the scratch gap width, 200 μm. (*p<0.05, **p<0.01);

[0026] Figure 5 It is an assessment of wound healing progress and comparison of healing times among different studies. Figure 5 (a) Schematic of the experimental timeline showing application of the wound dressing on day 0 followed by wound imaging and tissue sampling on days 3, 7, 10, and 14. (b) Representative images of wounds collected on days 0-14. Colored outlines indicate the wound area measured at each time point. Quantification of wound surface area (c) and wound size (d) throughout the experiment. *p<0.05 and **p<0.01.

[0027] Figure 6 The results of histological evaluation of wound healing in different experimental groups are shown. Figure 6 In the figure, (a) H&E and (b) Masson staining images of wound tissue were collected on the 7th and 14th days after treatment with OQG1, OQG2, and OQG3 hydrogels, respectively, and the gauze treatment was used as the blank group. The analysis based on these images included (c) epithelial cell layer score, (d) fibroblast score, (d) fibroblast score, inflammatory cell score, (f) newly formed capillary count, (g) dermal thickness (μm), and (h) hair follicle count, compared with the blank group. Statistical significance was *p<0.05, **p<0.01, ***p<0.001, respectively.

[0028] Figure 7Figure 2. Results of immunofluorescence analysis and wound healing mechanism analysis of different experimental groups. (a) Representative immunofluorescence images of wound sections of blank and treatment groups (OQG1, OQG2, OQG3) at 7 and 14 days after injury. Quantitative detection of the relative expression of TNF-α (b) and VEGF (c) in wound tissues at 7 and 14 days. (d) Description of the wound healing mechanism using synthetic OQG hydrogel as wound dressing. *p<0.05, **p<0.01, and ***p<0.001. DETAILED DESCRIPTION

[0029] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but do not limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several changes and improvements can be made without departing from the concept of the present invention. These all belong to the scope of protection of the present invention. In the present invention, room temperature refers to 20-30°C.

[0030] Example 1

[0031] A method for preparing a multifunctional conductive injectable hydrogel OQG in this embodiment is as follows: Figure 1 As shown, the following steps are included:

[0032] 1) Preparation of aldehyde-dextran (ODex)

[0033] 3.28 g NaIO 4 Add ultrapure water to obtain 0.0154M NaIO 4 The solution was gradually added with 400 mL of 1.25 wt / v% dextran aqueous solution Dex (0.0308 M), stirred at room temperature in the dark for 24 h, and then an equal amount of ethylene glycol was added to the system to neutralize the remaining NaIO 4 , using a dialysis membrane with a pore size of 3500Da, the obtained solution was dialyzed in ultrapure water for 3 days and then freeze-dried to obtain ODex. The obtained ODex was stored in a dark, dry place for future use. Figure 1 As shown in a.

[0034] 2) Preparation of quaternary ammonium chitosan (QCS)

[0035] In a three-necked flask, 16 g of chitosan (100 mmol) and 7.2 g of glycidyl trimethyl ammonium chloride GTMAC (50 mmol) were dispersed in 240 mL of ultrapure water, stirred and refluxed at 80 ° C for 36 h to obtain a yellow reaction product, which was dialyzed in ultrapure water with a 1.4 KDa dialysis membrane for 72 h, and concentrated and freeze-dried to obtain QCS; Figure 1 As shown in b.

[0036] 3) Preparation of polydopamine modified reduced graphene oxide (rGO@PDA)

[0037] 20 mg of graphene oxide (GO) and 20 mg of dopamine (DA) were dissolved in 40 ml of Tris·HCl buffer (pH=8.5), ultrasonicated for 30 min, and stirred vigorously at room temperature for 24 h. The reaction solution was separated, extracted, filtered, and the rGO@PDA composite was collected and vacuum dried at 60°C for 48 h. Figure 1 As shown in c.

[0038] 4) Preparation of composite OQG hydrogel

[0039] Composite OQG hydrogel was prepared using synthesized QCS, ODex and rGO@PDA nanoparticles. QCS was added to ultrapure water, stirred at 500 r / min for 8 hours at 37°C to obtain a 3wt% QCS solution, recorded as solution A; ODex was added to purified water and oscillated at room temperature in the dark to obtain a 12.5wt% ODex solution, recorded as solution B; DA was dissolved in ultrapure water and oscillated at room temperature in the dark to obtain a 20wt% DA solution, recorded as solution C. Then rGO@PDA nanoparticles were added to solution A, and solution B and solution C were mixed, stirred at 800 r / min at 37°C for 18 minutes to obtain mixed solution A and mixed solution B, respectively. The two mixed solutions were then mixed evenly and allowed to stand for 2 minutes to obtain OQG hydrogel, in which ODex and DA react to form ODex-DA (such as Figure 1 a), ODex-DA reacts with OQG uniformly mixed with rGO@PDA to form a hydrogel; the mass ratio of ODex:DA is 6:1, the mass ratio of rGO@PDA nanoparticles to QCS is 1:3, and the mass ratio of ODex of mixed solution B to QCS in mixed solution A is 1:1.

[0040] Example 2

[0041] The preparation method of a multifunctional conductive injectable hydrogel OQG in this embodiment is the same as that in Example 1, except that in step 4), rGO@PDA nanoparticles are added to the QCS solution and stirred at 35°C and 500 r / min for 3 h; the temperature when the quaternary ammonium salt chitosan QCS is added to water is 35°C, the stirring speed is 400 r / min, and the mixing time is 9 h;

[0042] The rGO@PDA nanoparticles were added to solution A, and solution B and solution C were mixed, and stirred at 800 r / min for 15 min at 37°C to obtain mixed solution A and mixed solution B, respectively. Then, the two mixed solutions A and B were mixed evenly and allowed to stand for 1 minute.

[0043] Example 3

[0044] The preparation method of a multifunctional conductive injectable hydrogel OQG in this embodiment is the same as that in Example 1, except that, in step 4), the three solutions are mixed, and then rGO@PDA nanoparticles are added and stirred at 1000 r / min at 40°C for 1 h; the temperature when the quaternary ammonium salt chitosan QCS is added to water and mixed is 40°C, the stirring speed is 600 r / min, and the mixing time is 8 h;

[0045] The rGO@PDA nanoparticles were added to solution A, and solution B and solution C were mixed, and stirred at 800 r / min for 20 min at 37 °C to obtain mixed solution A and mixed solution B, respectively. Then, the two mixed solutions A and B were mixed evenly and allowed to stand for 3 minutes.

[0046] Example 4

[0047] The preparation method of a multifunctional conductive injectable hydrogel OQG in this embodiment is the same as that in Example 1, except that AC@PDA is also added to the hydrogel; the mass ratio of the AC@PDA to rGO@PDA is 1:5; the AC@PDA is added directly to the quaternary ammonium chitosan QCS solution. Among them, the preparation of the polydopamine-loaded asiaticoside (AC@PDA) nanoparticles: synthesized in two steps, in the first step, dopamine (DA) is polymerized under alkaline conditions to generate PDA nanoparticles. To achieve this, 180 mg of DA powder was dissolved in 90 mL of ultrapure water and the pH was adjusted to 8.5 with 1 M sodium hydroxide solution. The resulting mixture was stirred at 25 ° C for 24 h to form a black precipitate. Subsequently, the PDA nanoparticles were collected by centrifugation at 4000 rpm for 15 min, washed with ultrapure water to remove residual sodium hydroxide, and freeze-dried to obtain black powder. The second step was to load AC onto PDA nanoparticles: 0.2 mg of freeze-dried PDA nanoparticle powder was dispersed in 10 mL of AC solution (AC content 2 mg / ml) to obtain a dispersion suspension, which was stirred at 4°C for 2 h to ensure the effective loading of AC, and then centrifuged and freeze-dried to obtain AC@PDA nanoparticles, which were stored at 4°C for future use. Figure 1 As shown in d.

[0048] Example 5

[0049] The preparation method of a multifunctional conductive injectable hydrogel OQG in this embodiment is the same as that in Example 4, except that the mass ratio of AC@PDA to rGO@PDA is 1:1.

[0050] Example 6

[0051] The preparation method of a multifunctional conductive injectable hydrogel OQG in this embodiment is the same as that in Example 4, except that the mass ratio of AC@PDA to rGO@PDA is 1:10.

[0052] Example 7

[0053] The preparation method of a multifunctional conductive injectable hydrogel OQG in this embodiment is the same as that in Example 4, except that the AC@PDA is added directly into the ODex solution.

[0054] Experimental Example 1: Structural Characterization and Performance Testing: Synthesis and Characterization of QCS, ODex, rGO@PDA and AC@PDA

[0055] The synthesis of QCS, ODex, nanoparticles rGO@PDA and AC@PDA was as follows Figure 1 As shown. Dex is NaIO 4 Oxidation yields Odex. In the infrared spectra of Dex and ODex, the peak is at 1731 cm -1 , indicating the presence of an aldehyde functional group ( Figure 2 a). In addition, there are Dex and Odex 1 H NMR showed chemical shifts between 3.2 and 5.4 ppm, indicating the presence of hydroxyl and methylene protons in Dex. The new chemical shift at 9.5 ppm was associated with the aldehyde functional group of ODex ( Figure 2 e). The present invention determines that the degree of oxidation (η) of ODex is 31.41±0.79%. During the preparation of OQG hydrogel, ODex-DA is formed by the Schiff base reaction between the aldehyde group of ODex and the amino group of DA, resulting in the grafting of DA onto the polysaccharide chain of ODex. The grafting rate can be used. This grafting rate will further affect the aldehyde reactivity and physicochemical properties of OQG hydrogel. In a series of preliminary experiments using different ratios of ODex and DA, a suitable reactivity was selected and the optimal ratio was determined to be ODex:DA=6:1. At this particular ratio, the grafting rate was 5.95% ( Figure 2 f).

[0056] QCS polymers ( Figure 1 b) CS and QCS 1 H NMR spectra showed that the chemical shifts at 3.2 and 3.5 ppm corresponded to trimethylammonium and -NH 2 ( Figure 2 g). In addition, the FT-IR spectrum of QCS is at 1475 cm -1 This is attributed to GMTAC ( Figure 2 The methyl group (CH) in b) is bent, which indicates that the QCS was successfully prepared.

[0057] In addition, PDA-modified reduced graphene oxide (rGO@PDA) nanoparticles were incorporated into OQG hydrogels with the aim of enhancing the hydrophilicity and electrical conductivity of the hydrogels ( Figure 1 c) FT-IR analysis of rGO@PDA shows a peak at 2962 cm -1 and 2873cm -1 , corresponding to the stretching vibrations of methyl and methylene, respectively. The results confirm the polymerization of dopamine and the existence of the PDA layer on the reduced graphene oxide. -1 There is no CO peak at , which is different from graphene oxide, which directly indicates the reduction of graphene oxide ( Figure 2 c). TEM shows the successful preparation of rGO@PDA nanoparticles, showing a layered structure ( Figure 2 h). In addition, XPS spectral analysis was used to determine the composition, chemical state, and molecular structure of the surface elements based on the position and shape of the peaks, and the content of the elements based on the intensity of the peaks. This analysis confirmed the effective synthesis of reduced graphene oxide@PDA nanoparticles by forming a PDA layer on reduced graphene oxide, while significant changes in elemental composition occurred throughout the synthesis stage ( Figure 2 k).

[0058] In the present invention, the encapsulation efficiency EE and drug loading efficiency DL of AC were 25.35±1.21% and 0.182±0.043 mg / mg, respectively, involving the cyclopolymerization of dopamine monomers to form PDA nanoparticles, followed by the loading of AC. Figure 1 As shown in d.

[0059] Experimental Example 2: Preparation and physicochemical properties of OQG hydrogel

[0060] OQG hydrogel was prepared based on ODex, OCS, DA and rGO@PDA, and imine bonds were dynamically formed between amino and ethyl groups. In the FT-IR of OQG hydrogel, the imine bonds were quantified at 1644 cm -1 There is a new absorption peak at , which is attributed to the stretching vibration of the C=N bond, confirming the existence of the Schiff base bond ( Figure 2 d).

[0061] The preparation methods of OQG1 hydrogel, OQG2 hydrogel and OQG3 hydrogel are the same as those of Example 1, except that: when preparing the gel, the mass ratio of ODex of mixed solution B to QCS in mixed solution A is different. The mass ratios of ODex of mixed solution B to QCS in mixed solution A in OQG1 hydrogel, OQG2 hydrogel and OQG3 hydrogel are 1:2, 1:1 and 3:2, respectively.

[0062] Compared with OQG1 and OQG2 hydrogels, the pores of OQG3 hydrogel have higher regularity and uniformity. The average pore size of all OQG hydrogels is between 200 and 350 μm, and the pore size of sample OQG1 is the lowest (about 200 μm) ( Figure 2 j).

[0063] The present invention evaluated the swelling properties of OQG hydrogels in PBS, such as Figure 3 As shown in a. The equilibrium swelling ratios of OQG1, OQG2, and OQG3 hydrogels after immersion in PBS were 646.2±69.0%, 521.0±61.2%, and 535.6±52.3%, respectively. The higher swelling ratio in OQG1 hydrogel indicates that its interpenetrating network and large pore structure are conducive to effective water absorption.

[0064] In addition, the OQG hydrogels of the present invention exhibited adhesion on human skin, glass, rubber gloves, and plastics, especially in dynamic areas with highly active features, such as joints ( Figure 3 b). The adhesion of OQG hydrogel is attributed to the presence of positively charged quaternary ammonium cations in QCS, as well as electrostatic forces between hydrogen bonding and hydrophobic bonding between skin tissue and QCS. Considering the practical application of hydrogels as wound dressings, the mechanical properties of the hydrogels were evaluated. The colloidal state of OQG hydrogels can also be determined by rheological analysis ( Figure 3 cg), and the elastic modulus (G') and viscosity modulus (G") were measured according to frequency, time, and strain, respectively. The results showed that the G' of all OQG hydrogels was higher than G" at lower frequencies, and decreased rapidly when the G' frequency reached a higher frequency ( Figure 3 c) The G' and G" of all OQG hydrogels remain at 1 rad·s -1 frequency, indicating the typical viscous flow characteristics of the hydrogel ( Figure 3 d). The G' values ​​of all OQG hydrogels were approximately 1500Pa. In contrast, the mechanical properties of OQG1 hydrogel significantly exceeded those of OQG2 and OQG3 hydrogels, which was due to the formation of Schiff base bonds, which increased the crosslinking density and improved the mechanical strength and structural integrity of the OQG hydrogels. This result was consistent with the strain amplitude scan, in which the OQG hydrogel network collapsed, and sample OQG1 hydrogel showed a larger strain (approximately 23.9%) than OQG2 and OQG3 hydrogels ( Figure 3 eg).

[0065] The self-healing properties of the hydrogel enhance the durability of the wound dressing. The present invention uses rheological analysis and macroscopic observation methods to study the self-healing properties of OQG hydrogel. The continuous step strain method is used to analyze the recovery rate behavior of OQG hydrogel ( Figure 3h). Under high strain conditions (100%), G" exceeded G', indicating that the structural network of the OQG hydrogel collapsed. This phenomenon was further confirmed by the significant decrease in G' and G" from 667Pa to 60Pa. However, when the hydrogels were under low strain (1%), they quickly recovered their original G' values, demonstrating their recovery ability. The cyclic test results showed that the OQG hydrogel had a high network recovery efficiency and had significant self-healing ability due to the Schiff base bond between the amine group (QCS) and benzaldehyde (ODex). In addition, a macroscopic self-healing test was performed in which two OQG hydrogel disks were cut at room temperature and put together again for 10 minutes, and they were completely healed without any external intervention. In addition, the hydrogels could be lifted after self-healing ( Figure 3 i). The hydrogel has good injectability and effectively fills irregular wounds. When squeezed and injected through a 2.5 mL syringe, no clogging was encountered. In addition, the injection performance of OQG hydrogel was evaluated by evaluating the dependence of OQG hydrogel on shear rate. Figure 3 j, the viscosity of the hydrogels decreased with increasing shear rate. Rheological analysis showed that all OQG hydrogels had special self-healing, shear-thinning and injectable properties.

[0066] The induction of antioxidant activity has a positive impact on wound healing by regulating the overproduction of reactive oxygen species (ROS). The ability of OQG hydrogels to scavenge free radicals was evaluated. Figure 3 k. The DPPH scavenging rates of all OQG hydrogels exceeded 20%, which may be due to the transfer of electrons or hydrogen atoms from the nitrogen ion segment to the DPPH radical. At 0.5h, OQG3 hydrogel showed higher antioxidant capacity and higher DPPH scavenging ability compared with OQG1 and OQG2 hydrogels. The antioxidant effect of these prepared OQG hydrogels makes them more suitable as wound healing dressings. When skin defects occur, the negative charges around the skin combine with the positive charges in the wound to generate an endogenous electric field, which plays an important role in cell migration during wound healing. Conductive hydrogels have water-rich, three-dimensional structures and conductive functions, and have received great attention in biomaterials science research. The conductivity of OQG hydrogels was evaluated ( Figure 3 l and 3m). Circuit board, two electrodes permeated with OQG hydrogel without physical contact, resulting in the illumination of a small light bulb, thus confirming the conductivity of all OQG hydrogels ( Figure 3 l). In general, electrical conductivity promotes the efficient transmission of electrical signals within biological tissues, thereby promoting wound healing.

[0067] Experimental Example 3: Antibacterial properties of OQG hydrogel

[0068] The present invention uses two complementary analytical methods to evaluate the antibacterial effect of hydrogels. In the first experiment, OQG hydrogel discs (4 mm in diameter and 1.5 mm in thickness) were prepared and sterilized by UV irradiation for 2 h. A 90 mm diameter nutrient agar (NA) plate was inoculated with 100 μL of a bacterial suspension (at a concentration of 10 ^7 CFU / mL) to ensure uniform distribution over the entire surface. Subsequently, the sterilized hydrogel discs were placed on the inoculated NA plates and incubated in a humidified environment at 37°C for 24 hours. After incubation, the diameter of the inhibition zone around the hydrogel discs was measured. In the second test, the antibacterial activity of OQG hydrogels in OQG Bertani (LB) broth medium was evaluated. The hydrogel samples (0.002 g) were added to glass tubes containing 10 mL LB medium and 10 μL of diluted bacterial suspension. The tubes were then incubated at 37°C for 12 hours, and their optical density at 600 nm (OD600) was measured using a UV-visible spectrophotometer. The bacterial suspension was cultured in LB medium without the hydrogel sample to establish a blank control group. The calculation formula for the inhibition rate is as follows:

[0069]

[0070] Where K b It's OD 600 The value of the blank control group, K s It's OD 600 The value of the sample group.

[0071] Results Figure 4 Both experiments show that the OQG hydrogel of the present invention has a relatively enhanced antibacterial effect.

[0072] Among them, in the first experiment, OQG2 had a good inhibitory effect on the growth of Escherichia coli, such as Figure 4 As shown in a, OQG3 has a good inhibitory effect on Staphylococcus aureus ( Figure 4 b). In the second liquid antibacterial test, there was no significant difference in the inhibitory effect of the three hydrogels on the growth of Escherichia coli. However, OQG2 had a significant inhibitory effect on Staphylococcus aureus ( Figure 4 c). It can be seen that OQG2 has a good antibacterial effect by effectively inhibiting the growth of the two strains.

[0073] Experimental Example 4: Biocompatibility of OQG hydrogel

[0074] The cell compatibility of hydrogels is an important parameter in the field of wound dressings. The present invention uses fluorescence microscopy images and CCK-8 detection to evaluate the cell compatibility of OQG hydrogels. The results are shown in Figure 4df. After NIH 3T3 cells were co-cultured with OQG hydrogel extract for 1 day and 3 days, live and dead cells were stained (Calcein-AM / PI). Fluorescence detection was performed at the same time to obtain the live and dead cells on day 1 ( Figure 4 d) and day 3 ( Figure 4 e) Staining photos. The spindle-shaped morphology of NIH 3T3 cells was normal, and the number of cells increased from day 1 to day 3, indicating that OQG hydrogel has good cell compatibility. After co-culture with OQG hydrogel extract at 37°C for 1, 3, and 5 days, its toxicity was detected by CCK-8 method. By analyzing and calculating the OQG hydrogel at 450nm (OD 450 ) to obtain the cell survival rate statistics as shown in Figure 4 f. It can be seen that the cell viability of all OQG hydrogels is stable within a few days. In addition, the present invention also uses the scratch method to study the cell migration ability of OQG hydrogels ( Figure 4 g). The cell migration rates of OQG1, OQG2, and OQG3 hydrogels were 53.59%, 52.83%, and 59.58%, respectively, which were higher than 50.79% of the control group. The results showed that OQG hydrogel promoted cell migration and enhanced the closure of cell scratches.

[0075] Experimental Example 5 In vivo wound healing performance

[0076] Experimental methods: Twenty-four adult female Sprague-Dawley (SD) rats weighing 250 ± 50 g were obtained and randomly divided into four groups: a control group and three experimental groups, namely OQG1, OQG2, and OQG3. The rats were allowed to acclimate to the surrounding environment in the cage for one week before the start of the experiment. During the surgery, the rats were anesthetized by intraperitoneal injection of sodium pentobarbital (3%, 50 mg / kg). After anesthesia, the back of the rats was shaved and disinfected with povidone-iodine. Then, a circular full-thickness skin wound with a diameter of 10 cm was made on the back of each rat using scissors. The wound was covered with OQG hydrogel in the experimental group, and the wound was treated with saline in the control group. Each wound was subsequently wrapped with gauze and fixed with a bandage. The rats were placed on a warm blanket until they recovered from anesthesia and were returned to their cages for postoperative care. Wound photographs were taken on days 0, 3, 7, 10, and 14 to monitor the healing process. On the 7th and 14th days, wound tissues were randomly sampled from each group for histological examination and staining.

[0077] The performance of OQG hydrogel as wound dressing was evaluated using a circular gross excision wound (15 mm in diameter) model in Spargue-Dawley (SD) rats. Figure 5 a).

[0078] In this experimental example, AC@PDA nanoparticles were added to the preparation of OQG1, OQG2, and OQG3 hydrogels to obtain OQG1, OQG2, and OQG3 encapsulated with AC@PDA nanoparticles. The addition method was the same as in Example 4, and the AC@PDA nanoparticles were in situ encapsulated into the OQG hydrogel, wherein the QCS / AC@PDA weight ratio was 5. During the wound healing process, the gauze group (blank control without hydrogel) had no obvious healing effect from day 0 to day 3, while the wounds of the OQG1, OQG2, and OQG3 hydrogel-treated groups shrank and began to crust. On the 7th and 10th days, the wound area of ​​the OQG hydrogel-treated group decreased, especially in the OQG1 hydrogel-treated group, where the wound healing speed was faster. On the 14th day, the gauze-treated group still had unhealed wounds, but the wounds treated with OQG hydrogel were basically healed ( Figure 5 b). In addition, the wound area of ​​each experimental group on different days was statistically analyzed ( Figure 5 b, 5c) and wound diameter ( Figure 5 d), it can be clearly seen that the healing speed of the OQG1 hydrogel-treated group is faster. Compared with the blank group, all OQG hydrogel-treated groups have the effect of promoting wound healing. The wound healing speed of the OQG hydrogel-treated group is faster than that of the gauze-treated group, which confirms that the OQG hydrogel encapsulated with AC@PDA nanoparticles can effectively promote wound healing as a wound dressing. Moreover, by comparing the wound healing time of different research groups, it is confirmed that the OQG experimental group of the present invention has the effect of accelerating wound healing. Among them, AC@PDA nanoparticles have the potential to promote scarless wound healing by stimulating collagen synthesis, reducing wound oxidation and accelerating cell proliferation. Substances such as AC used in wound dressings can promote tissue growth, accelerate granulation formation and wound healing.

[0079] Experimental Example 6 Histological Analysis

[0080] Analytical methods: Wound tissues were collected on days 7 and 14 after injury, fixed with 4% paraformaldehyde, embedded in paraffin, and sectioned (5 μm thick). For histological evaluation, sections were deaffinity, rehydrated, and stained for tissue structure using hematoxylin and eosin (H&E), and collagen deposition using Masson trichrome, including a series of staining steps to highlight various tissue components. Immunohistochemical analysis for TNFα and VEGF expression included deaffinity, antigen retrieval, blocking of endogenous peroxidase and nonspecific binding, application of primary and secondary antibodies, and detection using chromogenic substrates. Sections were observed and analyzed under a microscope. Histological examination was performed under high-powered fields. Based on the histological images obtained (five images per sample, five areas randomly selected), statistical methods were used to evaluate the epithelial cell layer, inflammatory cells, fibroblasts, number of newly formed capillaries, dermis, and hair follicles.

[0081] Results Figure 6 H&E and Masson staining results showed that the epidermis was still not fully formed in the blank group and the hydrogel-treated group after 14 days. Histopathological examination was used to evaluate the progress of wound healing after applying OQG1, OQG2, OQG3 hydrogels and gauze as a control for wound dressing.

[0082] In this experimental example, based on the preparation of OQG1, OQG2, and OQG3 hydrogels, AC@PDA nanoparticles were added to prepare OQG1, OQG2, and OQG3 encapsulated with AC@PDA nanoparticles. The adding method was the same as in Example 4, and the AC@PDA nanoparticles were in situ encapsulated into the OQG hydrogel, wherein the QCS / AC@PDA weight ratio was 5.

[0083] H&E staining ( Figure 6 a) and Masson staining ( Figure 6 The results of b) are consistent with the wound healing rate results proposed earlier. H&E and Masson staining results showed that the epidermis of the blank group and the QCS hydrogel-treated group was formed after 10 days. According to the epithelial cell layer score ( Figure 6 c), the scores of the OQG1, OQG2, and OQG3 hydrogel-treated groups were higher than those of the blank group on days 7 and 14, with the OQG1 hydrogel-treated group having the highest score. Among them, the OQG1 hydrogel-treated group promoted complete regeneration of the epidermis. In addition, fibroblasts were detected in all groups, and their number increased continuously from day 7 to day 14 ( Figure 6 d). On day 7, a large number of inflammatory cells, such as lymphocytes and macrophages, migrated to the wound area in all groups, causing an inflammatory response. The results showed that the blank group showed more inflammatory factors than the OQG hydrogel-treated group. During the course of days 7 to 14, the inflammatory cell scores of all groups decreased, and the scores of the OQG1 hydrogel-treated group were lower than those of the other groups ( Figure 6 e). In addition, the number of newly formed capillaries increased significantly from day 7 to day 14 ( Figure 6 f). Among all the groups, the OQG1 hydrogel-treated group showed more newly formed capillaries on both days 7 and 14. In the middle and late stages of the wound healing process, the regeneration of epidermal and dermal tissues indicated that the wound was completely healed. It can be observed that all OQG hydrogel-treated groups formed epidermis, although the extent of formation on day 14 was different, while the dermis of the OQG1 hydrogel-treated group was thicker than that of the other groups ( Figure 6 g).

[0084] Experimental Example 7: Histological and Immunohistochemical Evaluation

[0085] Figure 7 Immunohistochemical staining for TNF-α and VEGF expression ( Figure 7a), Statistical analysis of immunohistochemical evaluation ( Figure 7 b, c), Schematic diagram of skin wound healing ( Figure 7 d). It is shown that the hydrogel of the present invention is beneficial for promoting skin wound healing. The wound repair process was evaluated using immunofluorescence tests to detect inflammatory factors (TNF-α) and vascular endothelial growth factor (VEGF). First of all, controlling infection is the most important criterion for repairing infected skin lesions. TNF-α is an inflammatory cytokine, a cytokine involved in various inflammatory responses, used to induce T-cell proliferation, differentiation, etc. It plays an important role in the inflammatory response, so TNF-α was used to evaluate the inflammatory response of the wound tissue on the 7th and 14th days. Figure 7 a shows that the TNF-α evaluation scores of the hydrogel group were generally the same as those of the blank group. On the 14th day, the inflammatory response was significantly reduced. In addition, the difference in inflammation levels between the hydrogel group and the blank group was statistically significant on the 7th and 14th days (P<0.05). This shows that the hydrogel has the advantage of good anti-inflammatory properties in repairing infected skin. VEGF is a highly targeted pro-angiogenic factor that stimulates increased vascular permeability, extracellular matrix changes, migration, endothelial cell proliferation, and angiogenesis.

[0086] In this experimental example, based on the preparation of OQG1, OQG2, and OQG3 hydrogels, AC@PDA nanoparticles were added to prepare OQG1, OQG2, and OQG3 encapsulated with AC@PDA nanoparticles. The adding method was the same as in Example 4, and the AC@PDA nanoparticles were in situ encapsulated into the OQG hydrogel, wherein the QCS / AC@PDA weight ratio was 5.

[0087] like Figure 7 As shown in the immunofluorescence image in a, the fluorescence intensity of VEGF in the blank group was lower than that in the hydrogel-treated group. Quantitative analysis ( Figure 7 c) It was further confirmed that on the 7th and 14th days, the values ​​of the blank group were lower than those of the OQG1 hydrogel group, indicating that the OQG1 hydrogel has a good repair mechanism. In fact, the conductive and antibacterial properties of the hydrogel promote angiogenesis. The vascular system plays a vital role in providing adequate nutrition to damaged tissues and promoting wound repair. The schematic diagram of the wound healing mechanism of the prepared OGQ / AC@PDA hydrogel is shown in Figure 7 d. The electrical conductivity, antioxidant, and antibacterial properties of these substances in the hydrogel were observed to accelerate wound healing. In addition, the beneficial effects of AC in promoting angiogenesis, new hair follicle formation, and new collagen synthesis may help accelerate the regeneration of scar-free skin.

[0088] In summary, multifunctional conductive injectable hydrogels were prepared by adding rGO@PDA and AC@PDA nanoparticles between QCS amino groups and DA and ODex aldehyde groups under physiological conditions. The resulting OQG hydrogel has multifunctional properties such as tissue adhesion, good self-healing ability, injectability, biocompatibility, conductivity, antibacterial and antioxidant properties. PDA-loaded sinigrin nanoparticles were dispersed in OQG hydrogels and showed significant effects in promoting wound healing and achieving scarless regeneration. In conclusion, the multifunctional composite hydrogel of the present invention is also very suitable for treating irregular and active wounds and helps promote scarless wound healing.

Claims

1. A method for preparing a multifunctional conductive injectable hydrogel OQG, characterized in that: The following steps are involved: 1) adding water to quaternary ammonium salt chitosan QCS, aldehyde-dextran ODex and dopamine DA to obtain QCS solution, ODex solution and DA solution respectively; 2) Add rGO@PDA nanoparticles to the QCS solution, stir the DA solution and the ODex solution at 35-40°C and 500-1000 r / min for 15-20 min to obtain a mixed solution A and a mixed solution B; then mix the two mixed solutions A and B evenly and let stand for 1-3 min to obtain an OQG hydrogel.

2. The method for preparing the multifunctional conductive injectable hydrogel OQG according to claim 1, characterized in that: AC@PDA is also added into the hydrogel.

3. The method for preparing the multifunctional conductive injectable hydrogel OQG according to claim 1, characterized in that: The mass ratio of AC@PDA to rGO@PDA is 1:(1-10).

4. The method for preparing the multifunctional conductive injectable hydrogel OQG according to claim 1, characterized in that: The AC@PDA can be added directly into the quaternary ammonium salt chitosan QCS solution or the ODex solution.

5. The method for preparing the multifunctional conductive injectable hydrogel OQG according to claim 1, characterized in that: The AC@PDA nanoparticles are synthesized in two steps. In the first step, dopamine DA is polymerized under alkaline conditions to generate PDA nanoparticles. Specifically, 180 mg of DA powder is dissolved in 90 mL of ultrapure water, and the pH is adjusted to 8.5 with a 1 M sodium hydroxide solution. The obtained mixture is stirred at 25° C. for 24 hours to form a black precipitate. Subsequently, the PDA nanoparticles are collected by centrifugation at 4000 rpm for 15 minutes, washed with ultrapure water to remove residual sodium hydroxide, and freeze-dried to obtain a black powder. In the second step, the PDA nanoparticles are loaded with AC: 0.2 mg of freeze-dried PDA nanoparticle powder is dispersed in 10 mL of AC solution to obtain a dispersion suspension, and stirred at 4° C. for 2 hours. AC@PDA nanoparticles are obtained by centrifugal filtration and freeze-drying, and stored at 4° C. for later use.

6. The method for preparing the multifunctional conductive injectable hydrogel OQG according to claim 1, characterized in that: In step 1), the preparation step of the quaternary ammonium salt chitosan QCS is as follows: 16g chitosan and 7.2g glycidyl trimethylammonium chloride GTMAC are dispersed in 240mL ultrapure water, stirred and refluxed at 80°C for 36h to obtain a yellow reaction product, dialyzed in ultrapure water for 72h using a 1.4KDa dialysis membrane, and concentrated and freeze-dried to obtain QCS.

7. The method for preparing the multifunctional conductive injectable hydrogel OQG according to claim 1, characterized in that: In step 1), the aldehyde-dextran ODex is prepared by the following steps: 3.28 g of NaIO4 is added with water to obtain a 0.0154 M NaIO4 solution, 400 mL of a 1.25 wt / v% dextran aqueous solution Dex is gradually added, and the mixture is stirred and reacted at room temperature in the dark for 24 hours, and then an equal amount of ethylene glycol is added to the system to neutralize the remaining NaIO4. The obtained solution is dialyzed for 3 days and then freeze-dried to obtain ODex; a dialysis membrane with a pore size of 3500 Da is used for dialysis.

8. The method for preparing the multifunctional conductive injectable hydrogel OQG according to claim 1, characterized in that: In step 1), the rGO@PDA nanoparticles are prepared by the following steps: 20 mg of reduced graphene oxide (rGO) and 20 mg of dopamine (DA) are dissolved in 40 ml of Tris·HCl buffer (pH=8.5), ultrasonicated for 30-60 min, and vigorously stirred for reaction at room temperature for 24 h. The reaction solution is separated, extracted, and filtered to collect the rGO@PDA complex, which is then vacuum dried at 60°C for 48 h.

9. The method for preparing the multifunctional conductive injectable hydrogel OQG according to claim 1, characterized in that: In step 1), the temperature of quaternary ammonium chitosan QCS during mixing is 35-40°C, the stirring speed is 400-600r / min, the mixing time is 6-9h, and aldehyde-glucan ODex and dopamine DA are added with water and shaken at room temperature and protected from light to mix; in step 1), the concentration of the QCS solution is 3wt%, the concentration of the ODex solution is 12.5wt%, and the concentration of the DA solution is 20wt%; and in step 2), the mass ratio of the ODex:DA is 6:1, the mass ratio of rGO@PDA nanoparticles to QCS is 1:3, and the mass ratio of the ODex of the mixed solution B to the QCS in the mixed solution A is (0.5-1.5):

1.

10. The multifunctional conductive injectable hydrogel OQG prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Cited By

  • Quaternary ammonium salt modified chitosan-based composite hydrogel and preparation method thereof

    CN119775641A